Electrical and fotoconducting characterization of Al/coumarin:ZnO/Al novel organic-inorganic hybrid photodiodes - Aslan, Fehmi; Esen, Hikmet; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2019)
Coumarin doped ZnO/p-Si photodiodes were prepared by using the drop casting technique. The effect of coumarin contribution on the photoresponse properties of fabricated Al/Coumarin:ZnO/p-Si/Al organicinorganic hybrid devices was investigated. Electrical characterization of Al/Coumarin:ZnO/p-Si/Al photodiodes was carried out in the dark and under various illumination intensities with current-voltage (I-V) and capacity/conductivity-voltage (C-G-V) characteristics. The photocurrent of the diodes were found to be higher under illuminated conditions than the dark situation. It was determined that the prepared photodiodes exhibit photovoltaic behavior. Also, the photosensitivity properties of photodiodes were investigated. The highest photosensitivity expressed as (photo/(dark ratio was found as 894.73 for the specimen having 3% coumarin weight ratio under the conditions of 100 mW/cm(2) and 5 V. Transient photocurrent measurements confirmed that the photocurrent is sensitive to light intensity. In addition, capacitance/conductivity-voltage measurements were accomplished in frequencies between 10 kHz and 1 MHz. As a result of the continuous distribution of interface states, the capacity decreased with increasing frequency. It was determined that all photodiodes produced exhibit a linear photoconductivity behavior. The calculated ideality factors for Al/Coumarin:ZnO/p-Si/Al photodiodes prepared with various coumarin weight ratios exhibited that the non-ideal behaviors due to surface states and oxide layer. In addition, it was understood that the values of the barrier height and the interfacial density of the diodes could be changed with the doped of coumarin. As a result, it is concluded that the produced organicinorganic devices can be used as optical sensors for optoelectronic applications. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Coumarin:ZnO; Electrical properties; Photodiode; Organic-inorganic diode